2021
DOI: 10.1111/cns.13778
|View full text |Cite
|
Sign up to set email alerts
|

Impaired dynamic cerebral autoregulation is associated with the severity of neuroimaging features of cerebral small vessel disease

Abstract: Aims Cerebral small vessel disease (CSVD) is characterized by functional and structural changes in small vessels. We aimed to elucidate the relationship between dynamic cerebral autoregulation (dCA) and neuroimaging characteristics of CSVD. Methods A case‐control study was performed. Cerebral blood flow velocity (CBFV) of bilateral middle cerebral arteries and spontaneous arterial blood pressure were simultaneously recorded. Transfer function analysis was used to calculate dCA parameters (phase, gain, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…White matter hyperintensities (WMH), the most common morphologic feature on brain magnetic resonance imaging (MRI) in cerebral small vessel disease, is common among older people 1–3 . There is increasing evidence suggesting that WMH can cause cognitive decline and plays a significant role in the etiology of vascular cognitive impairment (CI) 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…White matter hyperintensities (WMH), the most common morphologic feature on brain magnetic resonance imaging (MRI) in cerebral small vessel disease, is common among older people 1–3 . There is increasing evidence suggesting that WMH can cause cognitive decline and plays a significant role in the etiology of vascular cognitive impairment (CI) 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…White matter hyperintensities (WMH), the most common morphologic feature on brain magnetic resonance imaging (MRI) in cerebral small vessel disease, is common among older people. [1][2][3] There is increasing evidence suggesting that WMH can cause cognitive decline and plays a significant role in the etiology of vascular cognitive impairment (CI). 4,5 However, individuals with WMH exhibit high levels of heterogeneity in cognitive performance, and a portion of these individuals even maintain normal cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms of the association between CSVD and ANS were not well‐elucidated; however, several possibilities were put forth as follows. Firstly, increased mechanical stress on the endothelium and subsequent endothelial injury induced by the imbalance between sympathetic and parasympathetic tones were presumed to contribute to the failure of dynamic cerebral autoregulation and blood–brain barrier disruption 50–52 . Secondly, the cerebrovascular architecture in the deep brain parenchyma lacked anastomoses; as a result, these regions were more susceptible to vasodilatory disturbances in rigid vessels caused by abnormal autonomic function 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, increased mechanical stress on the endothelium and subsequent endothelial injury induced by the imbalance between sympathetic and parasympathetic tones were presumed to contribute to the failure of dynamic cerebral autoregulation and blood–brain barrier disruption. 50 , 51 , 52 Secondly, the cerebrovascular architecture in the deep brain parenchyma lacked anastomoses; as a result, these regions were more susceptible to vasodilatory disturbances in rigid vessels caused by abnormal autonomic function. 53 Thirdly, many risk factors and mechanisms which were reported to be associated with HRV, such as diabetes and inflammation, were deemed to exert interactive effects that enhance the link between HRV and CSVD.…”
Section: Discussionmentioning
confidence: 99%
“…CSVD is associated with changes in cerebral small vessels and consequent brain damage in the white and grey matter [ 18 ]. A recent study in patients with CSVD demonstrated that CA was compromised, and some specific neuroimaging characteristics (total CSVD burden, white matter hyperintensities, severe PVS, and lobar cerebral microbleeds) might indicate more severe CA impairment [ 19 ]. Another study in patients with Alzheimer’s disease demonstrated an interrelationship between Alzheimer’s disease pathology, CSVD, and CA [ 20 ].…”
Section: Discussionmentioning
confidence: 99%